Biogenesis, functions, and clinical implications of circular RNAs in non-small cell lung cancer - Ying Liu (Elsevier, 2022)
Lung cancer (LC) is the leading cause of cancer-related deaths worldwide, with high morbidity and mortality. Non-small cell lung cancer (NSCLC) is a major pathological type of LC and accounts for more than 80% of all cases. Circular RNAs (circRNAs) are a large class of non-coding RNAs (ncRNAs) with covalently closed-loop structures, a high abundance, and tissue-specific expression patterns. They participate in various pathophysiological processes by regulating complex gene networks involved in proliferation, apoptosis, migration, and epithelial-to-mesenchymal transition (EMT), as well as metastasis. A growing number of studies have revealed that the dysregulation of circRNAs contributes to many aspects of cancer progression, such as its occurrence, metastasis, and recurrence, suggesting their great potential as efficient and specific biomarkers in the diagnosis, prognosis, and therapeutic targeting of NSCLC. In this review, we systematically elucidate the characteristics, biogenesis, and functions of circRNAs and focus on their molecular mechanisms in NSCLC progression. Moreover, we highlight their clinical implications in NSCLC treatment.